Efecto reparativo de Pastas Experimentales Anti-A / Estudio In Vivo - Gálvez Calla, Luis H. (2003)
Healing of a wound is fundamental answer of injured tissue that leads to restoration of tissue integrity, based on collagen synthesis, as a main protein of extra cellular matrix that contributes lo the invigoration wound. With the objective of solving in an integral approach bony defects post tooth extraction, it was postulated the use of natural products with anti-inflamatory and healing properties in pure or associate form. The study was made in cobayos (in vivo) first, in an experimental phase and then, in an applicative phase. 08 cobayos were considered without sex discrimination, of 30 to 40 days of age, divided in two groups: study group (07) and control group (01): experimental pastes were applied to them. Pastes had been introduced in tubes with holes, the time pastes setting was approximately 8 minutes. After general anesthesia, an area was shaved in a lateral back side of cobayos. Surgical arco was defined; infiltration of xylocaine 2% as a vasoconstrictor. A lineal incision in vertical sense was practiced of approximately 1 cm. Skin was debrided and separated of the subcutaneous tissue with a groove probe, creating a bed or bag for experimental pastes. After tissue reposition, it was proceeded to suture skin, in a simple suture, with silk thread 000 and curved atraumatic needle. Finally, the animals were placed in individual cages properly coded, for a period of 12 hours postoperative, being fed in a normal form. After 5 days of evolution of experimental pastes surgically implanted, the speciments of biopsy tissues show degrees of fibroblastic activity in areas of pastes diffusion, free inflamatorv signs. However a light level of inflammatory infiltrated cells llke plamacytes, neutrophi1s and macrophages were observed. In general pure liquid extracts of each natural product have shown a better anti-inflammatory and healing behavior that associated ones.